2008
DOI: 10.1016/j.cnur.2008.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and Barriers for Implementing Home Visit Interventions to Address Intimate Partner Violence: Town and Gown Partnerships

Abstract: Pregnant women involved in violent relationships represent a population that is vulnerable for poor pregnancy and infant outcomes on several levels. This article describes development of a 'town and gown' partnership to assist pregnant women in violent relationships. Barriers and facilitating factors for research and home visit nurse partnerships working with this vulnerable population were identified by home-visitor participants in a qualitative focus group session. Methods utilized to develop and maintain th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 41 publications
3
41
0
Order By: Relevance
“…Although 4 formal training programs, consisting of at least a halfday session, had been provided to all home visitors in all 12 programs, a fifth training session was planned and implemented. 17 Barriers and facilitators to screening were discussed, and the most common barriers discussed by home visitors included fear of either being a victim of violence from the abusive partner or having the client withdraw from HV because discussing IPV would be too sensitive and intrusive for participants. Thus, the study protocol was modified so that home visitors obtained only the woman' s consent to provide her name and contact information, to be given to the research team.…”
Section: Discussionmentioning
confidence: 99%
“…Although 4 formal training programs, consisting of at least a halfday session, had been provided to all home visitors in all 12 programs, a fifth training session was planned and implemented. 17 Barriers and facilitators to screening were discussed, and the most common barriers discussed by home visitors included fear of either being a victim of violence from the abusive partner or having the client withdraw from HV because discussing IPV would be too sensitive and intrusive for participants. Thus, the study protocol was modified so that home visitors obtained only the woman' s consent to provide her name and contact information, to be given to the research team.…”
Section: Discussionmentioning
confidence: 99%
“…Barriers to screening include provider discomfort with IPV questioning, fear of offending women, lack of training, confidentiality issues, and time restrictions [12-14]. Mobile health technology (mHealth) such as mobile phones and other wireless computing devices may offer a solution to some of these problems, as they can allow for more confidentiality, may be beneficial for women who are unwilling to disclose abuse to a health professional, and may help to standardize the way IPV assessments and interventions are delivered [15].…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that visitors reported multiple personal barriers to addressing IPV during their visits. These included: (a) fear of offending the client and having the client withdraw from services; and (b) not knowing what to do if IPV were disclosed (Eddy, Kilburn, Chang, Bullock, & Sharps, 2008;Jack et al, 2012;Sharps et al, 2013); (c) believing the formal training they received to be inadequate (Tandon, Parillo, Jenkins, & Duggan, 2005); and (d) not knowing how to assist clients in connecting with the resources they needed due to a lack of knowledge about the community services available (Eddy et al, 2008). As reported by Jack et al (2012), home visitors' lack of general knowledge and skills in identifying and responding to IPV was certainly noted by their clients.…”
Section: Early Prevention Home Visiting Programsmentioning
confidence: 99%